Morphological Changes in the Lungs in Brain Injuries (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The brain and lungs strongly interact via complex pathways from the brain to the lungs but also from the lungs to the brain. The main pulmonary disorders that occur after brain injuries are neurogenic pulmonary edema, acute respiratory distress syndrome, and ventilator-associated pneumonia, and the principal brain disorders after lung injuries include brain hypoxia and intracranial hypertension. All of these conditions are key considerations for management therapies after traumatic brain injury and need exceptional case-by-case monitoring to avoid neurological or pulmonary complications.